2005
DOI: 10.1128/iai.73.9.5612-5619.2005
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Specific CD4+T Cells Home to and Accumulate in the HumanHelicobacter pylori-Infected Gastric Mucosa

Abstract: Helicobacter pylori infects the stomach and duodenal mucosa. T cells are important components of the H. pylori-induced immune response, but little is currently known about how these cells are recruited to the infected mucosa. Here, we have characterized stomach and duodenal T cells isolated from H. pylori-infected and noninfected subjects with regard to subtype, expression of homing and chemokine receptors, and in vitro reactivity to H. pylori antigens. Higher numbers of CD4؉ but similar numbers of CD8 ؉ lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 45 publications
5
70
0
1
Order By: Relevance
“…All specimens were counterstained with Mayer's hematoxylin. The IHC results were considered to be positive when 10 Finally, sections were coverslipped with fluorescence mounting medium (DAKO). Stained sections were observed and photographed using a microscope BZ-9000 (Keyence, Osaka, Japan).…”
Section: Ihcmentioning
confidence: 99%
See 1 more Smart Citation
“…All specimens were counterstained with Mayer's hematoxylin. The IHC results were considered to be positive when 10 Finally, sections were coverslipped with fluorescence mounting medium (DAKO). Stained sections were observed and photographed using a microscope BZ-9000 (Keyence, Osaka, Japan).…”
Section: Ihcmentioning
confidence: 99%
“…7 The development of H. pylori-induced chronic gastritis depends predominantly on the Th1-type T-cell response. 8,9 The accumulation of H. pylori-specific CD4 þ T cells in the H. pylori-infected human gastric mucosa 10 suggests that CD4 þ T-cell-mediated Th1 immune responses have a critical role in the development of H. pylori-induced gastritis. Where CD4 þ T cells are primed by H. pylori antigens and how the H. pylori-induced chronic inflammation is maintained by T cells, however, are unclear because H. pylori appears not to be invasive and rarely infiltrates the gastric mucosa.…”
mentioning
confidence: 99%
“…pylori infection is atypical in that it causes a cellular infiltration of neutrophils and CD4 positive lymphocytes, as well as secretion of tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ). This response is characteristic of a T helper type 1 (Th1) immune response, which is typically associated with intracellular pathogens [10][11][12]. This observation prompted early vaccine research to focus on the induction of T helper type 2 (Th2) immunity, since it was suspected that Th1 immunity prevented clearance from the host.…”
Section: Introductionmentioning
confidence: 99%
“…In patients, H. pylori infection is associated with alterations in the profile of homing receptors expressed by peripheral blood T cells, directing their migration toward the inflamed gastric mucosa (Lundgren et al, 2005). We previously showed that H. pylori infection results in increased proportions of human peripheral blood Tregs that express the chemokine receptor CCR6 .…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of cases, however, colonization leads to asymptomatic chronic gastritis, with increased infiltration of neutrophils, dendritic cells (DCs), macrophages, natural killer (NK) cells, and lymphocytes into the gastric mucosa (reviewed in Robinson and Atherton, 2010;Koch et al, 2013). There is increased abundance of pro-inflammatory T-helper 1 (Th1) and Th17 subsets, as well as anti-inflammatory regulatory T cells (Tregs) (Lundgren et al, 2005;Robinson et al, 2008;Serrano et al, 2013). Infected individuals without gastroduodenal disease tend to have a more robust Treg response, which may also provide protection against extra-gastric conditions such as asthma, allergy, and inflammatory bowel disease (Kao et al, 2010;Arnold et al, 2011Arnold et al, , 2012Wang et al, 2013;Amberbir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%